Rare Pulmonary MALT Lymphomas and Its Differential Diagnosis On Chest CT - Tongzhen Xu MD; Shulan Zhang BA; Fang Liu MD (Journal of Investigative Medicine High Impact Case Reports)
Pulmonary nodules caused by mucosa-associated lymphomas (MALT lymphomas) are uncommon, comprising for less than 0.5% of all primary lung tumors. While biopsy is the main method for diagnosing the disease, the significance of differential pulmonary diagnosis based on imaging is often overlooked. In this report, we present a case of a patient with multiple disseminated nodules in the lungs, as well as severe anemia and incidental involvement of multiple lymph nodes. We discuss the differential diagnosis of pulmonary MALT lymphomas on computed tomography (CT) images and emphasize the significance of considering this uncommon entity in the evaluation of pulmonary nodules.